Closing Remarks - Lopez, Elise (Columbia Journal of Gender and Law, 2018)
Thank you all for coming. If you didn’t catch my name at the beginning, I’m Elise Lopez, the 2016–2017 President of Empowering Women of Color (EWOC). I just want to make a few closing remarks. First of all, I want to give a huge thanks to our panelists. They were phenomenal. I hope you enjoyed them as much as I did. Thank you very much.